Culture media to detect and criteria to evaluate and report the activity of extracellular enzymes produced by phytopathogenic fungi - Ferreira, Ana Beatriz Monteiro; Fischer, Ivan Herman; Leite, Luís Garrigós; Padovani, Carlos Roberto [UNESP]; Bueno, César Júnior (Instituto Biológico, 2019)
Extracellular enzymes are involved in the fungal pathogenesis in plants. Currently, culture media, data analyses, and data report related to extracellular enzymes produced in vitro conditions are different and therefore, lack standardization. This work aimed to compare the culture media cited on the literature (normal) with the potato-dextrose-agar (PDA) medium combined with a specific compound to produce extracellular enzymes through three soilborne phytopathogenic fungi (F. solani f. sp. passiflorae, S. rolfsii, and R. solani AG-4 HGI), as well as to analyze and report enzyme data based on five different criteria. The assay was randomized, with three factors (culture media, isolates, and enzymes) and six repetitions. The studied enzymes were amylase (AM), carboxymethylcellulase (CMCase), lipase (LP), laccase (LC), catalase (CT), and gelatinase (GT). The normal media detected more enzymes and was more precise compared to the PDA medium plus specific compound. The criteria that calculated the area of the circular crown of AM, CMCase, LP, and LC and measured the intensity (0 = absence, up to 4 = intense) of CT and GT adopting note scale were the best to evaluate and report the results of the enzymes. We suggest the normal media culture to study enzyme production, as well as the criteria mentioned to assess and report the data related to enzyme activities.

As enzimas extracelulares estão envolvidas na patogênese de fungos em plantas. Atualmente, não há uma padronização de meios de cultura, formas de analisar e divulgar os dados de enzimas extracelulares produzidas em condições in vitro. Assim, o presente trabalho objetivou comparar os meios de cultura específicos relatados na literatura (normal) com o meio de batata-dextrose-ágar mais adição do substrato específico para produção de enzimas extracelulares por três diferentes fungos fitopatogênicos habitantes de solo (Fusarium solani f. sp. passiflorae, Sclerotium rolfsii e Rhizoctonia solani AG-4 HGI), bem como avaliar os dados das enzimas por cinco critérios diferentes. O delineamento experimental adotado foi o inteiramente ao acaso, em esquema de três fatores (meios, isolados e enzimas), com seis repetições. As enzimas investigadas foram amilase, carboximetilcelulase, lipase, lacase, catalase e gelatinase. Os meios normais detectaram mais enzimas, e essa detecção foi mais precisa em comparação com os meios de batata-dextrose-ágar mais o substrato específico. Os critérios que calcularam a área da coroa circular para as enzimas amilase, carboximetilcelulase, lipase e lacase e adotaram a escala de notas para medir a intensidade (0=ausência até 4=intensa) de catalase e gelatinase foram os melhores para avaliar e divulgar os resultados das enzimas. Assim, sugere-se padronizar os meios normais para estudos de produção de enzimas, bem como os critérios citados para avaliar e divulgar os dados das atividades das referidas enzimas.
Meios de cultura para detectar e critérios para avaliar e divulgar atividade de enzimas extracelulares produzidas por fungos fitopatogênicos
Keywords: enzymes; soilborne phytopathogenic fungi; methodology; enzimas; fungos fitopatogênicos habitantes de solo; metodologia